Technology Entrepreneurship Project (ENT 600) : Philips Sdn. Bhd / Siti Nur Aishah Mohd Subardi - Mohd Subardi, Siti Nur Aishah (2021)
Philips Sdn. Bhd is a company that produces various types of home appliance products. Philips Sdn. Bhd is a public trading company founded by Gerard Philips on January 25, 1960. It is located in Petaling Jaya, Selangor, Malaysia. One of the products produced by Philips is blender is a kitchen and laboratory appliance used to mix, purée, or emulsify food and other substances. . The objective of this study is to analyze the problems faced by Syarikat Philips Sdn. Bhd. and provide better solutions to overcome these problems and give suggestions to companies in order to improve their company in the future. After doing company analysis, there are some problems that are based on the blender. In this study there are 3 Problems namely Unclear instruction, difficult bring anyway and noisy. Therefore, this study was released with three alternatives. The first alternative is are chargeable to make it easy to carry anywhere. The second alternative is a multifunction blender so that users use only one blender to make juice, ice blender, blender raw material sand cooking ingredients. The next alternative is size should produce a smaller size so that it is easy to carry anywhere and can be stored in a narrow place The last alternative is Blender 2 in1. Blender containers are not only for blenders but can make bottles so there is no need to use other containers to fill them. Therefore, this study was issued with the recommendation to choose one of the alternatives. This study suggests to choose to produce a blender. This is because the rechargeable blender is one of the alternative blender problems